2013
DOI: 10.1128/mbio.00856-13
|View full text |Cite
|
Sign up to set email alerts
|

MinC, MinD, and MinE Drive Counter-oscillation of Early-Cell-Division Proteins Prior to Escherichia coli Septum Formation

Abstract: Bacterial cell division initiates with the formation of a ring-like structure at the cell center composed of the tubulin homolog FtsZ (the Z-ring), which acts as a scaffold for the assembly of the cell division complex, the divisome. Previous studies have suggested that the divisome is initially composed of FtsZ polymers stabilized by membrane anchors FtsA and ZipA, which then recruit the remaining division proteins. The MinCDE proteins prevent the formation of the Z-ring at poles by oscillating from pole to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 53 publications
(79 reference statements)
6
41
0
Order By: Relevance
“…This argues for the following characteristics concerning the dynamics of FtsZ filament bundles: Once the protofilaments form a bundle, individual monomers or small protofilament fragments can dissociate and reassemble back to the bundle, resulting in a constant turnover. Recent in vivo studies also showed that the FtsZ counteroscillates to the Min waves in complex with bundling proteins such as ZipA or ZapA even at the early stages of ring assembly, suggesting that the FtsZ filaments already may be bundled (51). The extent of coupling between hydrolysis and depolymerization has been difficult to study experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…This argues for the following characteristics concerning the dynamics of FtsZ filament bundles: Once the protofilaments form a bundle, individual monomers or small protofilament fragments can dissociate and reassemble back to the bundle, resulting in a constant turnover. Recent in vivo studies also showed that the FtsZ counteroscillates to the Min waves in complex with bundling proteins such as ZipA or ZapA even at the early stages of ring assembly, suggesting that the FtsZ filaments already may be bundled (51). The extent of coupling between hydrolysis and depolymerization has been difficult to study experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…The oscillation of this system near the cell poles and away from midcell keeps the concentration of the MinC inhibitor lowest at midcell and highest at cell poles over time (14,17). This has the effect of preventing FtsZ from assembling near cell poles, visualized by the oscillation of FtsZ-green fluorescent protein (GFP)/cyan fluorescent protein (CFP) fusions from pole to pole in response (18)(19)(20).…”
mentioning
confidence: 99%
“…ZipA accomplishes this by promoting FtsZ bundling, as shown by reconstitution on lipid bilayers (56). In another study, ZapA-mediated bundling protected FtsZ from the depolymerizing effects of MinC (57).…”
Section: How Accessory Factors Focus the Z-ring In Spacementioning
confidence: 99%